Study of Working Hours of Indonesian Civil Servant Doctors in Relation to the Rule of Three Licenses for Practice and Labor Law - Noviana Indarti; SherlyIntan; Sylvia Meylinda; Tagor Sibarani; Mokhamad Khoirul Huda (Institute of Medico-legal Publications Pvt Ltd, 2022)
There are no specific rules about doctors’ working hours in Indonesia, it causes working hours ofIndonesian doctors to be excessive. Following the rules of the labor law that the maximum work of aworker is 40 hours a week. However, with the applicable 3 Licenses For Practice rules, the doctor’swork hours will be more than 40 hours a week. It was to examine whether the working hours ofIndonesian Civil Servant doctors are rational.Based on Law No. 13 of 2003 about Manpower article77 paragraph (2), the maximum working hours of a worker is 40 hours. In reality, with the 3 LicensesFor Practice rules, if it was calculated, the working hours of civil servant of doctors in Indonesia wasvery excessive. In other countries, there were already standard rules. Doctors work 40 hours a weekor a maximum of 80 hours a week. Therefore, it needed to be studied further, whether the 3 LicensesFor Practice policy had provided a solution or had actually aggravated the condition of a civil servantdoctor. The monoloyalty discourse of a doctor needed to be balanced with an increase in the services orincentives of a civil servant doctor.With the rule of three Licenses For Practice, the working hours ofcivil servant doctors in Indonesia became excessive.